Improved diagnosis of systemic lupus erythematosus with human-derived double-stranded DNA antigen - Li, Xianming; Tang, Honghu; Chen, Chunyan; Niu, Qian; Zhou, Zhen; Zheng, Yantong; Liu, Yi; Munoz, Luis Enrique; Herrmann, Martin; Wu, Peng; Zhao, Yi (Biosensors and Bioelectronics, 2025)
Anti-double-stranded DNA antibodies (anti-dsDNA) serve as a crucial serological indicator for systemic lupus erythematosus (SLE). Chemiluminescent immunoassay (CIA) is mainly used in clinical diagnosis of SLE, but suffers from low specificity, partially because the use of dsDNA antigens of varied sources in current CIA kits that sometimes led to controversial results. On the basis that anti-dsDNA in healthy individuals tend to selectively bind with dsDNA originating from pathogens, whereas pathogenic anti-dsDNA in SLE patients bind all forms of dsDNA, here we proposed the use of dsDNA fragment derived from human genome as antigen (synthesized via PCR using the human genomic DNA as the template). A magnetic bead-based immunofluorescence assay (IFA) was thus developed for SLE diagnosis, which exhibited improved sensitivity and specificity over CIA using the WHO reference reagent (15/174) as standard. For clinical serum sample analysis (n = 590), IFA exhibited an accuracy of 71.9% that was higher than CIA (65.3%). Crucially, the IFA results exhibited stronger correlations with the activity of SLE, renal involvement, and its prognosis. Besides the improved clinical diagnosis, the proposed IFA also holds great promise in assay standardization due to the high homogeneity of the synthetic dsDNA.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Anti-dsDNA antibody; Immunofluorescence assay; Standardization; Systemic lupus erythematosus